Process of Incorporation and Guidance in Public Health Systems for Protease Inhibitors in Chronic Hepatitis C in: a comparative case study between Brazil, Australia, Canada and England. - Fernanda Dias da SILVA; Claudia Cristina de Aguiar PEREIRA; Carla Jorge MACHADO (Universidade de Brasília, 2015)
Health Technology Assessment (HTA) studies subsidize decisions regarding the rational use of health technologies. Finding a balance between the sustainability of health systems, and proper access and use of technology, is a challenge and requires the use of consistent tools. In this paper we analyzed the general characteristics of the agencies or institutions responsible for HTA in Brazil, Australia, Canada and England and we carried out a comparative case study to understand the incorporation of protease inhibitors telaprevir and boceprevir for the treatment of chronic hepatitis C in these countries. For that purpose, we used electronic published reports found on the websites of those HTA agencies regarding telaprevir and boceprevir in 2013. Compared to other agencies, the Brazilian Commission (CONITEC) unlike the others, accepted the submission and published a single report for both drugs; the HTA model was homogeneous across countries. There were differences in the eligibility criteria and target population, despite the fact of drug approval; the price charged in Brazil was the lowest; the Brazilian CONITEC also set the criteria for healthcare using the drugs and for clinical protocols and therapeutic guidelines. Keywords: BiomedicalTechnology; Hepatitis C; ProteaseInhibitors